2021
DOI: 10.1002/term.3195
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff anchor repair: Histological changes associated with the recovering mechanical properties in a rabbit model

Abstract: Rotator cuff anchor repair is an increasingly common surgical procedure but the failure rate remains high. In order to improve surgical outcomes, a better understanding of postrepair histological and cellular responses at the tendon-bone attachment site (enthesis) is needed. We examined operated shoulders from 42 New Zealand female white rabbits. The animals underwent unilateral supraspinatus detachment followed by anchor repair a week later. To assess enthesis reformation, fibrocartilage staining area and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Very recently, Abraham et al (2022) 18 reported increased stiffness of the mouse supraspinatus tendon enthesis as well as increased PG content after downhill treadmill training. In addition, in a rabbit model of rotator cuff anchor repair, PG content was positively correlated with tendon supraspinatus stiffness, 4 weeks of post‐repair 65 . Further support is provided by the reported reduction in transverse compressive and axial tensile strains during ankle dorsiflexion, indicating a more rigid Achilles tendon enthesis, in patients with insertional Achilles tendinopathy 66 with, at the histological level, an increase in PG content 67 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Very recently, Abraham et al (2022) 18 reported increased stiffness of the mouse supraspinatus tendon enthesis as well as increased PG content after downhill treadmill training. In addition, in a rabbit model of rotator cuff anchor repair, PG content was positively correlated with tendon supraspinatus stiffness, 4 weeks of post‐repair 65 . Further support is provided by the reported reduction in transverse compressive and axial tensile strains during ankle dorsiflexion, indicating a more rigid Achilles tendon enthesis, in patients with insertional Achilles tendinopathy 66 with, at the histological level, an increase in PG content 67 .…”
Section: Discussionmentioning
confidence: 82%
“…In addition, in a rabbit model of rotator cuff anchor repair, PG content was positively correlated with tendon supraspinatus stiffness, 4 weeks of post-repair. 65 Further support is provided by the reported reduction in transverse compressive and axial tensile strains during ankle dorsiflexion, indicating a more rigid Achilles tendon enthesis, in patients with insertional Achilles tendinopathy 66 with, at the histological level, an increase in PG content. 67 The impact of PG on Achilles tendon stiffness is probably mediated by interactions of some of these macromolecules with collagens.…”
Section: Discussionmentioning
confidence: 92%